Post-Stabilization Economics in Sub-Saharan Africa. - Peiris, Shanaka J. (International Monetary Fund, 2008)
Mozambique is an economic success story in sub-Saharan Africa (SSA). Its remarkable achievements offer valuable lessons to other low-income countries in a post-stabilization economic phase, including how they can efficiently manage a scaling up of foreign aid aimed at poverty reduction. Of special interest to other sub-Saharan countries are the book's discussions of Mozambique's progress toward consolidating macroeconomic and financial stability, and the challenges it faces in ensuring long-term sustainability, creating a virtuous cycle of natural resource use, and implementing second-generati.